Upregulation of MTA1 in Colon Cancer Drives A CD8+ T Cell-Rich But Classical Macrophage-Lacking Immunosuppressive Tumor Microenvironment - Zhou, Yantong; Nan, Peng; Li, Chunxiao; Mo, Hongnan; Zhang, Ying; Wang, Haijuan; Xu, Dongkui; Ma, Fei; Qian, Haili (Frontiers in Oncology, 2022)
Background The MTA1 protein encoded by metastasis-associated protein 1 (MTA1) is a key component of the ATP-dependent nucleosome remodeling and deacetylase (NuRD) complex, which is widely upregulated in cancers. MTA1 extensively affects downstream gene expression by participating in chromatin remodeling. Although it was defined as a metastasis-associated gene in first reports and metastasis is a process prominently affected by the tumor microenvironment, whether it affects the microenvironment has not been investigated. In our study, we elucidated the regulatory effect of MTA1 on tumor-associated macrophages (TAMs) and how this regulation affects the antitumor effect of cytotoxic T lymphocytes (CTLs) in the tumor microenvironment of colorectal cancer. Methods We detected the cytokines affected by MTA1 expression via a cytokine antibody array in control HCT116 cells and HCT116 cells overexpressing MTA1. Multiplex IHC staining was conducted on a colorectal cancer tissue array from our cancer cohort. Flow cytometry (FCM) was performed to explore the polarization of macrophages in the coculture system and the antitumor killing effect of CTLs in the coculture system. Bioinformatics analysis was conducted to analyze the Cancer Genome Atlas (TCGA) colorectal cancer cohort and single-cell RNA-seq data to assess the immune infiltration status of the TCGA colorectal cancer cohort and the functions of myeloid cells. Results MTA1 upregulation in colorectal cancer was found to drive an immunosuppressive tumor microenvironment. In the tumor microenvironment of MTA1-upregulated colorectal cancer, although CD8+ T cells were significantly enriched, macrophages were significantly decreased, which impaired the CTL effect of the CD8+ T cells on tumor cells. Moreover, upregulated MTA1 in tumor cells significantly induced infiltrated macrophages into tumor-associated macrophage phenotypes and further weakened the cytotoxic effect of CD8+ T cells. Conclusion Upregulation of MTA1 in colorectal cancer drives an immunosuppressive tumor microenvironment by decreasing the microphages from the tumor and inducing the residual macrophages into tumor-associated microphage phenotypes to block the activation of the killing CTL, which contributes to cancer progression.